A case report of sirenomelia with two umbilical arteries: an unusual finding in a rare case - Trivedi, Swati; Nagar, Oby; Soni, J. P.; Trivedi, Shashank; Rastogi, Prasoon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Sirenomelia also known as Mermaid syndrome is a rarely encountered fusion anomaly of the caudal region of body often associated with Potter’s facies, single umbilical artery and various visceral abnormalities which make it irreconcilable with life. Here we report a case of sirenomelia delivered in our tertiary care hospital by lower segment cesarean section to a 24 year old third gravida with no previous live issues. No high risk factors could be identified with the mother including diabetes mellitus. Baby was born alive with Potter’s facies. Both the lower limbs were merging into each other like a mermaid’s tail (hence called mermaid syndrome). Sex of the baby could not be identified and the urogenital and anal orifices were absent. Umbilical cord stump had two umbilical arteries. The baby died after 20 hours of life. There appears to be no definitive modality for diagnosing sirenomelia in the antenatal period. However, if a patient has consistently low AFI without any history of leaking per vaginum, high resolution USG or colour Doppler should be done at the earliest to look for the cause.